The Co-operative Societies Law in Bangladesh: From Hope of Autonomy to Dependence - Islam, Md Rizwanul; Ahmed, Nafiz (Dhaka University Law Journal, 2022)
Abstract not available Dhaka University Law Journal, 2022, 33(1), 1-22